PENGARUH INVESTASI ASET TETAP DAN BIAYA OPERASIONAL TERHADAP PENDAPATAN OPERASIONAL PADA PT. SANSHIRO HARAPAN MAKMUR - Mukmin, Mas Nur; Gusprasetyo, Gusprasetyo (Fakultas Ekonomi Universitas Djuanda, 2017)
Research the purpose of this is to determine the influence of Fixed Assets Investment and Operating Expenses to Operating Income simultaneously and partially in PT Makmur Sanshiro expectations. This research is classified as causal research. Analysis of data using multiple linear regression . The results showed, simultaneously Fixed Asset Investment and Operating Costs Operating affect the revenue. Only partially influenced Operating Cost to Operating Income.Keywords: Fixed Asset Investment, Operating Expenses, Operating Income